Factorisable Monoid of Generalized Hypersubstitutions of Type τ=(2): Ampika Boonmee, Sorasak Leeratanavalee - Team, Support (Thai Journal of Mathematics, 2015)
A generalized hypersubstitution of type τ maps any operation symbol to the set of all terms of the same type which does not necessarily preserve the arity. Every generalized hypersubstitution can be extended to a mapping on the set of all terms. We define a binary operation on the set of all generalized hypersubstitutions by using this extension. It turns out that this set together with the binary operation forms a monoid. In this paper, we characterize all unit elements and determine the set of all unit regular elements of this monoid of type τ = (2). We conclude a submonoid of the moniod of all generalized hypersubstitutions of type τ = (2) which is factorisable.